Madurella mycetomatis, the main causative agent of eumycetoma, is highly susceptible to olorofim. (6th January 2020) - Lim, Wilson; Eadie, Kimberly; Konings, Mickey; Rijnders, Bart; Fahal, Ahmed H; Oliver, Jason D; Birch, Mike; Verbon, Annelies; van de Sande, Wendy
Abstract: Objectives: Eumycetoma is currently treated with a combination of itraconazole therapy and surgery, with limited success. Recently, olorofim, the lead candidate of the orotomides, a novel class of antifungal agents, entered a Phase II trial for the treatment of invasive fungal infections. Here we determined the activity of olorofim against Madurella mycetomatis, the main causative agent of eumycetoma. Methods: Activity of olorofim against M. mycetomatis was determined by in silico comparison of the target gene, dihydroorotate dehydrogenase (DHODH), and in vitro susceptibility testing. We also investigated the in vitro interaction between olorofim and itraconazole against M. mycetomatis. Results: M. mycetomatis and Aspergillus fumigatus share six out of seven predicted binding residues in their DHODH DNA sequence, predicting susceptibility to olorofim. Olorofim demonstrated excellent potency against M. mycetomatis in vivo with MICs ranging from 0.004 to 0.125 mg/L and an MIC90 of 0.063 mg/L. Olorofim MICs were mostly one dilution step lower than the itraconazole MICs. In vitro interaction studies demonstrated that olorofim and itraconazole work indifferently when combined. Conclusions: We demonstrated olorofim has potent in vitro activity against M. mycetomatis and should be further evaluated in vivo as a treatment option for this disease.